Performance assessment for generalized delay-timers in alarm configuration. (September 2017) - Zeng, Zhiyong; Tan, Wen; Zhou, Rong
Highlights: A new method to compute FAR, MAR and EDD for alarm configuration techniques that can be modeled via Markov chains is proposed. Explicit formulae to compute the performance indices of generalized delay-timer are given. Advantages of generalized delay-timer are compared with conventional delay-timer using industrial data. Abstract: False and nuisance alarms are major problems in the process industry. Generalized delay-timer is an effective technique to improve the performance of an alarm system. However, due to the increasing intermediate states, computation of the performance indices, false alarm rate (FAR), missed alarm rate (MAR) and expected detection delay (EDD), is hard and unsolved for generalized delay timer. In this paper, we first propose general formulae to compute FAR and MAR by adequately reconsidering the internal relationship between the no-alarm state and the alarm state. Then the computation of EDD is discussed via the probability of alarm or no-alarm at one sample by iteration. Simulation and industrial results show that alarm performance can be improved via generalized delay-timer with proper choice of the order.